Analysis of the Role of the Sukoharjo Regency Land Office (ATR/BPN) in Controlling the Conversion of Agricultural Land to Achieve Food Security - Annissa Dwi Febrianti (Faculty of Law, Universitas Negeri Semarang, 2025)
Food security is a crucial element in realizing sustainable development of a country. In this case, government institutions also have a role in striving for food security in a country. In Indonesia, the land office Atr/Bpn has this role. This study aims to analyze the factors that cause the conversion of agricultural land in Sukoharjo Regency and evaluate the role of the Land Office (ATR/BPN) in the control process. This study uses a qualitative approach with an empirical legal type, and data is obtained through interviews, document studies, and field observations. The results of the study indicate that land conversion is influenced by economic factors such as high land sales value, social factors in the form of population growth and urbanization, and regulatory factors and spatial planning policies. In addition, the development of strategic areas also drives conversion, coupled with the ongoing land sale and purchase process that occurs without a thorough examination of the zoning status. ATR/BPN Sukoharjo plays a role in control by providing technical considerations and involvement in spatial planning forums. This study recommends strengthening coordination between technical sections within the ATR/BPN environment, increasing cross-agency synergy, and consistent policy implementation so that agricultural land is maintained sustainably.